2021
DOI: 10.3389/fmars.2021.790929
|View full text |Cite
|
Sign up to set email alerts
|

Seascape Genomics Reveals Metapopulation Connectivity Network of Paramuricea biscaya in the Northern Gulf of Mexico

Abstract: The degree of connectivity among populations influences their ability to respond to natural and anthropogenic stressors. In marine systems, determining the scale, rate, and directionality of larval dispersal is therefore, central to understanding how coral metapopulations are interconnected and the degree of resiliency in the event of a localized disturbance. Understanding these source-sink dynamics is essential to guide restoration efforts and for the study of ecology and evolution in the ocean. The patterns … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 111 publications
1
13
0
Order By: Relevance
“…biscaya, respectively. Lineage 1 was generally found deeper (mean depth 1,896 m) than lineage 2 (mean depth 1,454 m); however, these lineages co-occur at some intermediate-depth sites and 15% of assessed specimens had an admixed ancestry (see Figure 1 in Galaska et al, 2021). Interestingly, the morphology of the specimens examined in this study differs between these two lineages, with P. aff.…”
Section: Molecular Analysesmentioning
confidence: 62%
See 4 more Smart Citations
“…biscaya, respectively. Lineage 1 was generally found deeper (mean depth 1,896 m) than lineage 2 (mean depth 1,454 m); however, these lineages co-occur at some intermediate-depth sites and 15% of assessed specimens had an admixed ancestry (see Figure 1 in Galaska et al, 2021). Interestingly, the morphology of the specimens examined in this study differs between these two lineages, with P. aff.…”
Section: Molecular Analysesmentioning
confidence: 62%
“…The need for robust species delimitation analyses is exemplified by a recent population genomic study of P. biscaya in the Gulf of Mexico, which utilized some of the same samples herein (Galaska et al, 2021). Based on >12K SNPs, Galaska et al (2021) found two lineages of P. biscaya, lineage 1 and lineage 2, represented in our study as P. cf. biscaya and P. aff.…”
Section: Molecular Analysesmentioning
confidence: 86%
See 3 more Smart Citations